Correlation between hepatitis B surface antigen and virus factors in chronic hepatitis B patients in Hospital Tengku Ampuan Afzan, Kuantan, Pahang - Hadi, Qabas Neamah (Kulliyyah of Medicine, International Islamic University Malaysia, 2016)
Recently, hepatitis B virus antigen (HBsAg) level has been used as a cheaper marker than molecular methods, not only for indicating active hepatitis B infection but also for predicting the clinical and treatment outcomes. However, data correlating HBsAg level with other diagnostic markers in Malaysia are inadequate to investigate the legitimacy of using HBsAg level as a surrogate or complementary serological marker for chronic hepatitis B (CHB) patients. Therefore, the goals of this study were to quantify HBsAg level in CHB patients and investigate its correlation with immune status (exemplified by peripheral blood lymphocytes'PBL' subset counts), HBeAg, anti-HBe, viral DNA load, HBV genotypes, and the presence of precore (G1896A) mutations.Methodology:A total of 50 CHB cases and 20 healthy controls were recruited for this cross-sectional study. Serum samples from cases were evaluated for both serological and virological parameters. The HBsAg concentrations for all patients were measured using Roche's Elecsys HBsAg II assay. The immune status for both study populations were evaluated by estimating the percentage and count of PBL. Viral DNA from all patients' sera was used for subsequent molecular tests such as PCR assay for HBV DNA detection and genotyping. Real time PCR with SYBR green assay was also performed for viral DNA quantification. Lastly, precore mutants of HBV were detected using high resolution melting analysis. The data were analysed to discover the relationship between HBsAg levels and the other parameters. Results: Viremic CHB patients exhibited narrowly higher mean levels of bilirubin and liver enzymes than the controls. The study of peripheral blood lymphocytes revealed that the percentage of CD4+& CD8+cells were significantly reduced in the patients' while CD4+/CD8+ ratio has increased. The measurement of HBsAg titers showed that the first group which represents 56% of patients are those with HBsAg levels of >1000 IU/mL, while, second group with <1000 IU/mL represents 44% of CHB patients. Specific viral S small gene DNA was identified in most patients (n=35) and the phylogenetic tree analysis for these samples elucidated that the sequences were classified as genotypes C & B with prevalence rates 54.2% for genotype C and 45.7% for genotype B. In the viral load study, a total of 15 out of 35 patients have a high viral DNA load≥ 3×106genome copies/mL, while 7 patients were regarded having a low viral load < 3× 106 genome copies/mL. The remaining 13 patients were categorised as undetectable viral DNA load (3× 103 copies/mL). The correlation outcomes showed that a higher number of patients with low-HBsAg level are positive for anti-HBe antibodies. In addition, there is a positive correlation between surface antigen levels with elevated ALT enzyme, and significant positive and negative correlations have been found between HBsAg titres and the percentage of total T and NK cells respectively. The analysis of association between HBV genotypes and HBsAg levels revealed that patients with genotype C have the higher serum level of this protein than genotype B. Other finding has showed no significant relationship between viral DNA copy number and HBsAg level. The precore (G1896A) variants of HBV were detected in only 25% of patients who tested negative for HBeAg but did not illustrate any correlation with HBsAg titres. Conclusion:The overall outcomes presented in this study are conducive to the importance of quantitative HBsAg serum level as a clinical complementary laboratory biomarker for managing and predicting chronic hepatitis B virus infection progression in the Malaysian' tested patients.